The Role of the Akathist by Metropolitan Tryphon (Turkestanov) “Glory to God for All Things” in Preserving the Orthodox Worldview in Russian Culture of the 20th — Early 21st Centuries - Maria R. Nenarokova; Natalya V. Nalegach (Вестник Екатеринбургской духовной семинарии, 2022)
The proposed article deals with understanding the text of the akathist by Metropolitan Tryphon (Turkestanov) “Glory to God for All Things” (1929). The role of the akathist in the preservation of the Orthodox spiritual values is noted both in the era of persecution of the Church in Soviet Russia and in modern times, marked by the strengthening of the positions of mass culture. The given Akathist was created in full accordance with the genre of canon, but for the language, which causes controversy about its value in modern society, as evidenced by the monitoring of Orthodox forums. The analysis of Akathist in the context of its author’s biography and theological views suggests that the choice of the Russian language is conditioned by Vladyka Tryphon’s desire to convey Christian consolation to those separated from the Orthodox ritual culture and its liturgical language. This hypothesis is supported by the figurative-thematic structure of Akathist and its intertexts. The title “Glory to God for All Things” is noteworthy. It was used as a prayer formula by the Byzantine saint John Chrysostom, the Optina elder Macarius and the Petrograd New Martyr Metropolitan Veniamin. The choice of Akathist’s title combines the spiritual experience of Byzantium, Russian Elder tradition, and of the years of persecution in the first half of the 20th century. The high values of meekness, Christian love, faith and hope, embodied in the text of Metropolitan Tryphon’s prayer, act as universal spiritual support for a human being in the world. It ensures the preservation and affirmation of the values of the Orthodox worldview in any historical and cultural situation unfavourable for the religious tradition.